Writing and Publishing High-Value Scientific Papers for Teachers - John Rafafy Batlolona; Marleny Leasa; Albertus Fenanlampir; Edy Janter Latumahina (Pascasarjana Universitas Mataram, 2026)
This community service activity aims to improve teachers' understanding and skills in writing and publishing systematic and high-quality scientific papers. The target group was 31 teachers at State Senior High School 14, Central Maluku, who participated in four days of training using training, discussion, and hands-on mentoring. The activity process included pre-writing, writing, and post-writing stages, beginning with a pre-test and ending with a post-test to measure the improvement in participants' competency. The results of the activity showed a significant improvement in the understanding of scientific paper structure, the ability to develop article outlines and drafts, and increased teacher confidence in writing and publishing scientific papers. Questionnaire data showed a high level of positive responses for most indicators, although several aspects still need improvement, such as understanding plagiarism and publication confidence. In addition, this activity also encouraged collaborative interactions between teachers and fostered an academic culture within the school environment. In conclusion, this training was effective in improving teachers' scientific writing competency, but follow-up in the form of ongoing mentoring and advanced training is needed to achieve more optimal and equitable results